2018
DOI: 10.1002/14651858.cd011492.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the treatment of brain radionecrosis after radiotherapy or radiosurgery

Abstract: There is a lack of good certainty evidence to help quantify the risks and benefits of interventions for the treatment of brain radionecrosis after radiotherapy or radiosurgery. In an RCT of 14 patients, bevacizumab showed radiological response which was associated with minimal improvement in cognition or symptom severity. Although it was a randomised trial by design, the small sample size limits the quality of data. A trial of edaravone plus corticosteroids versus corticosteroids alone reported greater reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Targeted agents after SRS for the brain have also been continued and have prolonged survival outcomes for patients with BM [6,7,9,15,16]. Radiation therapy has long been associated with the development of radiation necrosis (RN) in patients with intracranial disease [17][18][19][20][21]. The rate of RN following radiotherapy or radiosurgery has been estimated at 10-15% [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Targeted agents after SRS for the brain have also been continued and have prolonged survival outcomes for patients with BM [6,7,9,15,16]. Radiation therapy has long been associated with the development of radiation necrosis (RN) in patients with intracranial disease [17][18][19][20][21]. The rate of RN following radiotherapy or radiosurgery has been estimated at 10-15% [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy has long been associated with the development of radiation necrosis (RN) in patients with intracranial disease [17][18][19][20][21]. The rate of RN following radiotherapy or radiosurgery has been estimated at 10-15% [17][18][19][20][21]. RN is considered as a dose-limiting toxicity for SRS [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who are asymptomatic can be observed, while those who are symptomatic are managed with corticosteroids, hyperbaric oxygen therapy (HBOT), bevacizumab, pentoxifylline, vitamin E, laser-induced thermal therapy and/or surgery. [6][7][8][9][10] A recent Cochrane systematic review showed paucity of data on the topic, and was only able to include three comparative studies that used bevacizumab, edaravone and vitamin E. 11 HBOT is a non-invasive treatment that may stabilise necrosis, promote tissue repair and expedite neurological recovery. 12,13 Small retrospective studies have demonstrated high rates of benefit with either rates of stability or improvement estimated at 70%-80% of treated patients.…”
Section: Introductionmentioning
confidence: 99%